Feasibility of monitoring advanced melanoma patients using cell‐free DNA from plasma. (23rd October 2017) - Gangadhar, Tara C.; Savitch, Samantha L.; Yee, Stephanie S.; Xu, Wei; Huang, Alexander C.; Harmon, Shannon; Lieberman, David B.; Soucier, Devon; Fan, Ryan; Black, Taylor A.; Morrissette, Jennifer J. D.; Salathia, Neeraj; et al.
Summary: To determine the feasibility of liquid biopsy for monitoring of patients with advanced melanoma, cell‐free DNA was extracted from plasma for 25 Stage III/IV patients, most (84.0%) having received previous therapy. DNA concentrations ranged from 0.6 to 390.0 ng/ml (median = 7.8 ng/ml) and were positively correlated with tumor burden as measured by imaging (Spearman rho = 0.5435, p = .0363). Using ultra‐deep sequencing for a 61‐gene panel, one or more mutations were detected in 12 of 25 samples (48.0%), and this proportion did not vary significantly for patients on or off therapy at the time of blood draw (52.9% and 37.5% respectively; p = .673). Sixteen mutations were detected in eight different genes, with the most frequent mutations detected in BRAF, NRAS, and KIT . Allele fractions ranged from 1.1% to 63.2% (median = 29.1%). Among patients with tissue next‐generation sequencing, nine of 11 plasma mutations were also detected in matched tissue, for a concordance of 81.8%.